(untitled) (International Journal of Engineering and Computer Science, 2014)
This paper presents a novel matrix converter based drive technique for three phase brushless DC (BLDC) machines. In contrast to existing matrix converter based drives, the proposed technique uses a topology that has less number of semiconductors and a unique switching sequence to drive three phase BLDC machines directly from single phase mains supply lines without a DC link capacitor. The paper describes in detail both the topology and the unique switching sequence that is essential for the proposed technique. A model based on Matlab/Simulink is also presented to demonstrate the theoretical performance of the proposed drive system. The performance of the technique is evaluated using a model of 320 W BLDC machine, which is operated in both torque and speed control modes, and simulated results indicate that the performance of the machine is comparable to existing techniques. The proposed technique is simple to implement, cost effective with low component count, and can be easily adapted to applications such as PM synchronous motor drives or loads, which require a single to 3-phase power conversion.